Nanoparticlized System: Promising Approach for the Management of Alzheimer’s Disease through Intranasal Delivery - Bahadur, Shiv; Sachan, Nidhi; Harwansh, Ranjit K.; Deshmukh, Rohitas (Current Pharmaceutical Design, 2020)
Alzheimer's disease (AD) is a neurodegenerative brain problem and responsible for causing dementia in aged people. AD has become most common neurological disease in the elderly population worldwide and its treatment remains still challengeable. Therefore, there is a need of an efficient drug delivery system which can deliver the drug to the target site. Nasal drug delivery has been used since prehistoric times for the treatment of neurological disorders like Alzheimer's disease (AD). For delivering drug to the brain, blood brain barrier (BBB) is a major rate limiting factor for the drugs. The desired drug concentration could not be achieved through the conventional drug delivery system. Thus, nanocarrier based drug delivery systems are promising for delivering drug to brain. Nasal route is a most convenient for targeting drug to the brain. Several factors and mechanisms need to be considered for an effective delivery of drug to the brain particularly AD. Various nanoparticlized systems such as nanoparticles, liposomes, exosomes, phytosomes, nanoemulsion, nanosphere, etc. have been recognized as an effective drug delivery system for the management of AD. These nanocarriers have been proven with improved permeability as well as bioavailability of the anti-Alzheimer’s drugs. Some novel drug delivery systems of anti-Alzheimer drugs are under investigation of different phase of clinical trials. Present article highlights on the nanotechnology based intranasal drug delivery system for the treatment of Alzheimer’s disease. Furthermore, consequences of AD, transportation mechanism, clinical updates and recent patents on nose to brain delivery for AD have been discussed.
Keywords: novel drug delivery